Natural Pest Control: Evaluating Liquid Attractants for Snail and Slug Management - Satyawan Madrewar; Ashish Madhukar Rajnor; Atharva Manish Gumphekar; Ajay Rajaram Sagar; Ganesh Subhash Chandankar (International Journal of Global Sustainable Research, 2024)
The research involved three consecutive trials for each attractant, with traps placed in areas with high snail and slug activity. Glucose, when reacted with yeast, emerged as the most effective attractant, capturing an average of 26 snails/slugs per trial. Beer was the second most effective, with an average capture rate of 17. Sucrose and fructose, both reacted with yeast, performed similarly, with average capture rates of 12.33 and 12, respectively. Statistical analysis using ANOVA and Tukey's HSD test confirmed the significant differences between the attractants, particularly highlighting the superior performance of glucose.The findings suggest that glucose, when combined with yeast, could serve as a potent natural alternative for managing snail and slug populations, offering a safer and more sustainable option compared to chemical pesticides. Beer also shows promise as an effective attractant, particularly in regions where glucose may not be readily available. These results support the potential integration of these natural attractants into broader pest management strategies, aligning with the goals of sustainable agriculture. Future research should explore the long-term efficacy of these attractants and their impact on non-target species to ensure their suitability for widespread use.